STEM EDUCATION IN HIGH SCHOOLS: INFORMATION TECHNOLOGY AND WIRELESS NETWORKS - Hodges, Alexander Logan (East Carolina University, 2021)
With the COVID-19 pandemic that has moved so many of our lives virtual, the importance of IT and wireless networks has never been clearer. As virtual living become a bigger component of day-to-day life, so to does the importance of mobility and flexibility, benefits which wireless networks bring. Wireless networks are becoming the new norm, often replacing the wired networks of yesteryear. However, STEM and networking education, particularly in areas with fewer resources, have been slow to catch up, with a much heavier emphasis on wired networks and only a minor inclusion of wireless in most cases. While understanding wired networks is crucial to understanding basic networking functions, and wired networks is still widely used, it is important to educate the incoming IT workers of newer technologies. Possibly more important is gathering their interest in the field; with high school students being so enveloped in the wireless world, providing education and information that focuses on wireless and the computers in their pockets may attract some of the newest, brightest minds to the field, be it in the workforce or the field of study. This report details the project undertaken to do just this, and explores the process used to create lessons and hands-on activities to educate and entice. Along the way, it will also explore successes, difficulties, lessons, learned, and improvements and next steps for the project.
Keywords: wireless; education; STEM; IT